Nephrogenic Diabetes Insipidus: Effects of 3, 5, Cyclic-adenosine Monophosphate. Issue 255 (October 1972) - Jones, N. F.; Barraclough, M. A.; Barnes, N.; Cottom, D. G.
Abstract : In view of the evidence that the actions of vasopressin are mediated by the release of adenosine 3, 5, cyclic monophosphate (`cyclic-AMP'), the effects of this nucleotide were studied in 3 children with nephrogenic diabetes insipidus (NDI) who were insensitive to vasopressin. Intravenous injections of cyclic-AMP reduced urine flow in 2 of the 3 patients, but did not increase urinary osmolality nor the urinary concentrations of sodium, creatinine, and urea. In these respects the antidiuresis differed from that normally produced by vasopressin. The reduction in urine flow produced by cyclic-AMP was probably related to a fall in glomerular filtration rate associated with the prominent circulatory effects of the nucleotide. These effects appear to preclude the use of cyclic-AMP as an antidiuretic agent in the treatment of NDI.